Image analysis 17th Scandinavian Conference, SCIA 2011, Ystad, Sweden, May 2011 : proceedings - Heyden, Anders; Kahl, Fredrik (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 16th Scandinavian Conference on Image Analysis, SCIA 2011, held in Ystad, Sweden, in May 2011. The 74 revised full papers presented were carefully reviewed and selected from 140 submissions. The papers are organized in topical sections on multiple view geometry; segmentation; image analysis; categorization and classification; structure from motion and SLAM; medical and biomedical applications; 3D shape; medical imaging.